Beyond social-ecological traps: fostering transformations towards sustainability - Hampus Eriksson (Resilience Alliance, 2021)
This Special Feature is motivated by the rigorous, and growing, theoretical and empirical body of literature on social-ecological traps. Building on the foundational literature, which describes the context in many of the places where we work, we now look forward and ask how we can better understand and enable the breaking and escaping of social-ecological traps. In this Special Feature we focus on this frontier in the field and use the trap metaphor as a unifying framework for collating empirically derived insights on overcoming challenges across diverse geographies, sectors, and social-ecological contexts. We requested contributions to this feature that, as well as possible under each context, explore tangible pathways for disrupting social-ecological traps. Thematic relevance and clear contribution to social-ecological scholarship was emphasized in the invited contributions, but authors were not constrained by methodological approach, context, geographical location, or sector. Our ambition with this editorial is to synthesize the novel insights these papers highlight and situate their contributions within the relevant literature.